ผู้มีสิทธิฟ้องคดีปกครอง : ศึกษากรณีการผังเมือง - สาธร พงศ์ธรพิสุทธิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
This thesis aimed to study the concepts and principles of law related to subjects with the rights in suing city planning cases of Administrative Court both in Thailand and foreign coutries, and analyzing legal problems related to city planning administrative cases of the Thai legal system, including to obtain legal problems solutions in urban planning administrative litigation of Thai legal system in accordance with the city planning Act BE 2562. Although the city planning was a form of urban planning at all levels in having appropriate operation and management model. However, the announcement of the city plan had affected the people’s land using which will affect to those in the area of the city plan announcement in unavoidable suffered or damaged. According to section 42 of the Act on Establishment of Administrative Courts and Administrative Procedures BE 2542, they can sue the Administrative Court. However, the study results had shown that the rights in suing city planning cases of Administrative Court of some juristic persons are still unclear in case acceptation of the Administrative Court in city planning cases which if compared to foreign countries such as France and Germany that had guaranteed rights of juristic persons with the member’s interests protection or conserving natural resources and city planning purposes in suing the city plan cases.